2008
DOI: 10.1002/jso.21159
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and prognosis of hepatocellular carcinoma: A population based study in France

Abstract: HCC with and without cirrhosis has a poor prognosis with the majority of patients receiving palliative treatments, the efficiency of which is very limited. Considerable efforts are needed to develop primary and secondary prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
49
0
10

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 25 publications
(22 reference statements)
6
49
0
10
Order By: Relevance
“…While Milan or UCSF criteria were not fully implemented during period A (2000)(2001)(2002)(2003), there was no change over time that suggested any difference. Similar figures are reported in other surveys [20]. In a study where 28% of the tumours were detected by screening, 25% were treated with a curative aim [21] -the same results should be achievable in a Swedish population with liver disease if every person were to be thoroughly screened.…”
Section: Discussionsupporting
confidence: 79%
“…While Milan or UCSF criteria were not fully implemented during period A (2000)(2001)(2002)(2003), there was no change over time that suggested any difference. Similar figures are reported in other surveys [20]. In a study where 28% of the tumours were detected by screening, 25% were treated with a curative aim [21] -the same results should be achievable in a Swedish population with liver disease if every person were to be thoroughly screened.…”
Section: Discussionsupporting
confidence: 79%
“…This is consistent with the findings reported by Turakhia et al (29), which indicated that HSP27 reduced the doxorubicin-induced toxicity in cardiac cells by enhancing superoxide dismutase activity, and therefore protected the integrity of aconitases from superoxide-induced inactivation (29). According to the results of previous studies, the inhibition of HSPs has been established to have an impact on the growth of several malignant cell lines, including breast cancer (30) and leukemia (31). Furthermore, HSPs are known to form a complex with mutant p53, which allows tumor cells to bypass normal mechanisms of the cell cycle arrest.…”
Section: A B Csupporting
confidence: 89%
“…Standard treatments for localized HCC include surgical resection, liver transplantation,1, 2 radiofrequency ablation (RFA),3, 4 and transcatheter arterial chemoembolization (TACE) 5, 6, 7. Treatment eligibility is dependent on patient and tumor conditions.…”
Section: Introductionmentioning
confidence: 99%